(untitled) (Per Musi, 2018)
In 1836, inspired by the writings of the German philosopher Imannuel Kant and disillusioned with Unitarianism, Ralph Waldo Emerson and others founded the Transcendentalist Club in Concord, MA. The Transcendentalists defended Kant’s notion that knowledge was innate and believed that all lives emanated divinity, being bonded through a kind of universal soul. The writings of the Transcendentalists arguably helped shape the New England consciousness. Although composer Stuart Saunders Smith was born more than one hundred years after Transcendentalism’s heyday, as a New Englander, his life has been immersed in a culture that inherited values that trace back to this movement. This essay explores one of the movement’s principal features: the avoidance of teleology (i.e. goal-oriented thinking). Non-teleology is reflected in his music through his recent tendency of writing evening-length pieces, his frequent references to New England imagery, his disregard of form, his use of repetitions, his use of non-sequiturs, and his incursions of modality. The Starving Month for solo vibraphone, analyzed in the final section of this essay, presents all aforementioned characteristics.